Search for long-lived neutral particles produced in pp collisions at √s=13 TeV decaying into displaced hadronic jets in the ATLAS inner detector and muon spectrometer - Aad, Georges; Andrei, George Victor; Bolz, Arthur; Dunford, Monica; Ferreira de Lima, Danilo Enoque; Franchino, Silvia; Helary, Louis; Henkelmann, Lars; Jongmanns, Jan; Klassen, Martin; Krishnan, Anjali; Kugel, Andreas; et al. (Physical review, 2020)
A search is presented for pair production of long-lived neutral particles using 33 fb(-1) off root s = 13 TcV proton-proton collision data, collected during 2016 by the ATLAS detector at the LHC. This search focuses on a topology in which one long-lived particle decays in the ATLAS inner detector and the other decays in the muon spectrometer. Special techniques are employed to reconstruct the displaced tracks and vertices in the inner detector and in the muon spectrometer. One event is observed that passes the full event selection, which is consistent with the estimated background. Limits are placed on scalar boson propagators with masses from 125 GeV to 1000 GeV decaying into pairs of long-lived hidden-sector scalars with masses from 8 GeV to 400 GeV. The limits placed on several low-mass scalars extend previous exclusion limits in the range of proper lifetimes c tau from 5 cm to 1 m.
Das s steht im Titel unter dem Wurzelzeichen
ATLAS Collaboration: G. Aad, V. Andrei, A.E. Bolz, M. Dunford, D.E. Ferreira de Lima, S. Franchino, L. Helary, L. Henkelmann, J. Jongmanns, M. Klassen, A. Krishnan, A. Kugel, T. Mkrtchyan, F. Napolitano, P.S. Ott, M. Sahinsoy, A. Schoening, H.-C. Schultz-Coulon, T.M. Spieker, R. Stamen, P. Starovoitov, S. Suchek, L. Vigani, S.M. Weber, M. Wessels, X. Yue und 2906 weitere
Gesehen am 28.04.2020